2012
DOI: 10.1094/mpmi-06-12-0150-r
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Transcriptional and Anatomical Analyses of Tolerant Rough Lemon and Susceptible Sweet Orange in Response to ‘Candidatus Liberibacter asiaticus’ Infection

Abstract: Although there are no known sources of genetic resistance, some Citrus spp. are reportedly tolerant to huanglongbing (HLB), presumably caused by 'Candidatus Liberibacter asiaticus'. Time-course transcriptional analysis of tolerant rough lemon (Citrus jambhiri) and susceptible sweet orange (C. sinensis) in response to 'Ca. L. asiaticus' infection showed more genes differentially expressed in HLB-affected rough lemon than sweet orange at early stages but substantially fewer at late time points, possibly a critic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
118
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(124 citation statements)
references
References 44 publications
6
118
0
Order By: Relevance
“…Symptoms are mainly due to the host response itself: no genes that produce toxic compounds have been found in the genome sequence, the bacteria is a biotroph endophyte, and typical symptoms, such as asymmetric yellowing, starch accumulation, and callose production are directly linked to altered source-sink relationships due to altered expression of key genes involved in carbohydrate metabolism. Microarray analysis of artificially infected mature leaf tissues has been conducted to examine gene regulation in response to CaLas attacks under controlled conditions (Albrecht and Bowman, 2008;Kim et al, 2008;Fan et al, 2011Fan et al, , 2012. Recently, next-generation sequencing (NGS) technologies have been applied to characterize the fruit from afflicted trees (Martinelli et al, 2012) and to examine how the pathogen transcriptionally regulates source-sink relationships (Martinelli et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Symptoms are mainly due to the host response itself: no genes that produce toxic compounds have been found in the genome sequence, the bacteria is a biotroph endophyte, and typical symptoms, such as asymmetric yellowing, starch accumulation, and callose production are directly linked to altered source-sink relationships due to altered expression of key genes involved in carbohydrate metabolism. Microarray analysis of artificially infected mature leaf tissues has been conducted to examine gene regulation in response to CaLas attacks under controlled conditions (Albrecht and Bowman, 2008;Kim et al, 2008;Fan et al, 2011Fan et al, , 2012. Recently, next-generation sequencing (NGS) technologies have been applied to characterize the fruit from afflicted trees (Martinelli et al, 2012) and to examine how the pathogen transcriptionally regulates source-sink relationships (Martinelli et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The HLB infected stem exhibited cell wall thickness and collapse were observed in phloem, and the symptoms were more severe in stem than in root [19]. The phloem was damaged in HLB tolerant rough lemon and susceptible sweet orange at the similar level, but phloem transportation was maintained much better in rough lemon [20]. The damage of cell wall and cell membrane in phloem by CLas was caused by movement of pathogen between cells [21].…”
Section: Citrus Responses To Hlb Infectionmentioning
confidence: 99%
“…It could be hypothesized that tolerance in Rough lemon to HLB may be from the minimized influence in phloem transportation and fast response to CLas by comparing transcriptional profiling with susceptible sweet orange at 5, 17 and 27 WAI (weeks after inoculation) [20]. Another microarray study showed that the HLB tolerant US-897 had more genes involved in pathogen defense expression at higher level without CLas infection compared to susceptible 'Cleopatra mandarin' .…”
Section: Can Crispr Win the Battle Against Huanglongbing?mentioning
confidence: 99%
“…Quantitative real-time PCR (qPCR) was performed using a QuantiTect SYBR Green PCR Kit (Qiagen). Gene expression analysis was conducted by the comparative C T method as previously described (Fan et al 2012). Reverse transcription (RT)-PCR was carried out using Easy-Taq DNA Polymerase (TransGen Biotech).…”
Section: Reverse Transcription-pcr and Quantitative Real-time Pcrmentioning
confidence: 99%
“…Rice OsActin was used as 17 the reference gene. Relative gene expression was calculated by the comparative C T method as described(Fan et al 2012).…”
mentioning
confidence: 99%